The essential rights linked to the consumer through Advertising - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Advertising is a broad concept, apprehended late by the law, it is intended to make known and to sell a product or a service. It takes many forms, and the advertiser is considered responsible for the advertising, when it comes to the content. Thus, the main role of advertising is to inform the consumer about the characteristics of the product or service. At the same time, it isprohibited when it can mislead or abuse the consumer. This deception, whether intentional or not, constitutes an offence that may lead to the suppression of the advertisement.